Os gestos na comunicação mãe-bebê: um estudo longitudinal - Camargo, Janaina Franciele (2013)
This study aimed to analyze the nonverbal communication of mother-infant dyads during the first year of life, specifically at six, nine and 12 months of age. The frequency with which mothers and babies used deictic and representational gestures in each stage was verified, as well as maternal responses to the baby s communicative gestures and the contexts in which they were observed. In addition, it was analyzed the maternal meaning attributions regarding to gestures and other baby s communicative behaviors, such as crying, smiling and gaze direction. According to the social interaction perspective, adopted by this study, the child's language development occurs through interactions established with the adult since the early ages. Considering that babies are active since birth, these interactions are designed to be bidirectional, so that both components of the dyad act in modifying the context and behavior of each other. The participants were six dyads, four baby boys and two girls. The six dyads were recorded longitudinally when babies were six, nine and 12 months old, twice in each evolutionary period, totaling 36 observations. Each video contained 20 minutes of observation of the dyad in a free play situation. Ten minutes were transcribed, disregarding the first five and the final five minutes. The videos were analyzed through the literal transcription of speech and vocalizations of the dyad, as well as the detailed description of the context and the behavior of the mother and baby during the observation sessions. In addition to establishing categories of deictic and representational gestures and subsequent counting their frequency, a detailed analysis of the contexts in which such gestures were used was performed. The results showed that changes occur, especially at nine months. The reaching gesture is no longer the single category used by the child and shall be replaced by the pointing gesture. It was also noticed that the representational gestures, both conventional and object gestures, were observed only after that age. The deictic gestures most used in the establishment and maintenance of interactive episodes were reaching, by the babies, and showing, by mothers. Furthermore, behaviors such as crying, smiling and gaze direction, which form part of the basis of child s pre-verbal communication, proved to be very effective in changing the mother s behavior. It was noticed that mothers adjusted their behavior according to the baby s characteristics, so that changes in the child gestures during its development were accompanied by changes in maternal gestures and meaning attributions. These results are relevant in the sense that contribute to a greater knowledge about mother-infant gestural communication and its role in the child's linguistic development.